Adapting News Production to Social Media Logics as a Revenue Strategy: The Case of Beritabali.com - Asih, Irsanti Widuri; Eddyono, Aryo Subarkah (JURNAL KOMUNIKASI INDONESIA, 2025)
Over the past decade, news consumption has increasingly shifted from websites to social media, leading to a significant decline in advertising revenues for online news outlets. This shift presents a serious challenge for small-scale local media in Indonesia, which typically operate with limited financial and human resources. This study explores how Beritabali.com, a local news outlet, responds to these challenges by addressing three central questions: why it produces content for social media, how it adapts to the social media ecosystem, and what implications arise from this transformation. Drawing on the theory of deep mediatization and employing a qualitative methodology through in-depth interviews, the study finds that although Beritabali.com maintains its core news content on its website, it also produces tailored content for social media. This strategy is intended to attract advertisers as a source of revenue and to reach audiences who increasingly access news through social media platforms. To implement this strategy, Beritabali.comaligns with the logic of social media while continuing to uphold journalistic values. Given its financial and human resource limitations—both in terms of quantity and quality—the outlet engages interns with digital content production skills and adopts artificial intelligence (AI) tools to support content creation. The findings highlight the adaptive strategies employed by local media in a social media-driven environment and demonstrate how deep mediatization demands both technological innovation and shifts in newsroom culture.